Adaptive Complexities and Evolutionary Paradigms in Market Dynamics for Theoretical Exploration - Hamed, Ameera Fares; Salman, Riyadh Yousuf; Mahdi, Saad; Khalil, Ziyad Tariq (Journal of Ecohumanism, 2024)
Background: This academic article acknowledges the intricate interactions between numerous elements that shape economic systems as it examines market dynamics via an evolutionary perspective. The dynamic and adaptive character of markets is frequently ignored by traditional economic theories, calling for a paradigm change in favor of an evolutionary viewpoint. Objective: This study's main goal is to clarify the evolutionary processes affecting market dynamics. Our goal is to develop a complete framework that captures the complex evolutionary processes influencing market structures and behaviors by integrating insights from economics, sociology, and biology. Methods: This research uses a multidisciplinary approach to analyze the evolutionary forces at work in market dynamics by synthesizing actual data, current literature, and computational models. Our conceptualization of markets as dynamic ecosystems takes evolutionary biology into account, taking into account elements like competition, adaptation, and selection. Results: According to our research, market players adapt to shifting circumstances and competitive pressures in ways that are similar to biological evolution. Market structures are shaped by evolutionary processes, which also affect the dynamics of innovation, market entry, and exit. The study also identifies important factors that function as evolutionary catalysts in the evolution of markets, such as legislative changes and technology advancements. Conclusion: Evolutionary viewpoints provide important insights into comprehending the intricate and ever-changing character of markets. Understanding markets as dynamic systems enables a more nuanced understanding of economic events and lays the groundwork for creating flexible policies and tactics that are in line with the natural evolutionary dynamics of markets. By bridging the gap between conventional economic theories and the changing realities of modern marketplaces, this research helps.